Cost-utility analysis of a potential lung cancer screening program for a high-risk population in Germany: A modelling approach. (October 2018) - Hofer, Florian; Kauczor, Hans-Ulrich; Stargardt, Tom
Highlights: Lung cancer screening using LDCT for heavy smokers can be regarded as cost-effective. First CEA on LDCT screening that uses cost data from German payers. Underlying model is transparent and easy to understand for decision makers. Model can be easily adapted to other countries. Abstract: Background: Lung cancer is the leading cause of cancer death in Germany. Although several randomized trials in Europe have evaluated the effectiveness of lung cancer screening programs, evidence on the cost-effectiveness of lung cancer screening is scarce. Objective: To evaluate the cost-effectiveness of a population-based lung cancer screening program from the perspective of a German payer. Methods: We conducted a cost-effectiveness analysis from the public payer perspective for a high-risk population defined as heavy former and current smokers (≥20 cigarettes per day) between 55 and 75 years of age. The underlying model consisted of two Markov models. We differentiated between a population-based annual screening program and standard clinical care. Depending on stage at diagnosis, simulated patients were assigned to one of five treatment paths according to the German clinical guideline for the diagnosis and treatment of lung cancer. Costs, life years saved, and quality adjusted life years (QALYs) were used as outcomes. Values for input parameters were taken from the literature. The model was run for 60 cycles with a cycle length of three months. Deterministic and probabilistic sensitivity analyses were conducted. Results: In the base case, annual lung cancer screening led to an increase in incremental costs (€ 1, 153 per person) compared to standard clinical care. However, the screening approach was associated with an incremental gain in life years (0.06 per person) and QALYs (0.04 per person). Thus, the incremental cost-effectiveness ratio (ICER) was € 19, 302 per life year saved and € 30, 291 per QALY. A probabilistic sensitivity analysis with 10, 000 draws resulted in average ICERs of € 22, 118 per life year and € 34, 841 per QALY. Conclusion: We provide evidence that lung cancer screening for a high-risk population may be more effective, but also more costly, than standard clinical care from the perspective of a German payer.